Acid and Bile Tolerance of Lactobacillus thermotolerans, a Novel Species Isolated from Chicken Feces - Piyanuch Boonkumklao; Parichart Kongthong; Apinya Assavanig (Agriculture and Natural Resources, 2006)
Five strains of a novel thermotolerant lactic acid bacterium, Lactobacillus thermotolerans, isolated from chicken feces were assayed for acid and bile tolerance. Cultures of L. thermotolerans were grown anaerobically at 42°C in four different conditions, Man-Rogosa-Sharpe (MRS) broth at pH 6.5, MRS broth at pH 3.0, MRS broth supplemented with 0.3% (w/v) ox gall and MRS broth supplemented with 7 mM sodium taurocholate, respectively. All strains showed an acid tolerance when incubated at pH 3.0 over a period of 4 h. L. thermotolerans demonstrated significant changes of absorbance (p<0.05) from the control when cultured with 0.3% bile concentration. Strain JCM11427 seemed to show the highest tolerance to bile. However, statistical analyses revealed no significant differences. The conjugated bile salt (sodium taurocholate) at physiological concentration (7 mM) had no effect on growth of the bacterial strains.